STUDY AND ANALYSIS OF OPTICAL AND ELECTRICAL PROPERTIES TiX:Zn(1-X)O MATERIALS AND THE APPLICATION IN PHOTODETECTOR - ZUHAIRAH (NIM : 10213050), NABILAH
Global warming issue, mostly about ozone layer’s leakage is the main reason to study ultraviolet photodetector (UVPD), because it will detect the over intensity of UV radiation on Earth. A photodetector is needed to has several properties; it must be sensitive in some given spectral region, high responsivity and quantum efficiency, has fine photocurrent linearity, also has wide band gap energy. One of materials that belongs to the wide band gap energy group is Zinc Oxide (ZnO). In this research, we grew and characterize Titanium (Ti) doped Zinc Oxide, or TZO, materials, hopefully will increase the material’s sensitivity to the light and suitable for photodetector application. In this Final Project report, we had studied some journals and books about TZO materials, photodetector applications, also the growth method and some characterizations we used which are Spectroscopic Ellipsometry and UV-Vis to analyze the optical properties, also I-V Characteristics to get the electrical response of the materials to the light. Here, we had already grown TZO materials with Titanium concentrations respectively 0.5%, 0.4%, and 0.6%. The concentrations confirmed through EDX is not the same as expected from the target pellets due to the inability of controlling the concentration that grew on the substrates through deposition process. By using DC-Unbalanced Magnetron Sputtering (DC-UBMS) and several characterizations, we confirm that Titanium dopant will shift the band gap energy to the lower side and increasing the sensitivity of materials to the light.